PHILOSOPHICAL REVIEW OF TRADITIONAL DRY LAND GARDEN MANAGEMENT (LEL METO) THE DAWAN ( TUNBABA) TRIBE IN OESENA VILLAGE, MIOMAFFO EAST DISTRICT , NORTH TIMOR CENTRAL DISTRICT - Emanuel Tati Taena (Sean Institute, 2022)
Culture local considered as something already ancient and out of date, one example is in agriculture. Meup mutual cooperation system taboo Farmers for gardening and traditional garden management techniques have begun to fade and are replaced by modern work systems, the use of technology, and the excessive use of pesticides which will slowly destroy soil fertility. Atonic Society Pah Meto ( mountain people ) in Tunbaba, North Central Timor District , partly big is farmer land dry with system land move and slash burn. Planting process plant in the land dry Public Tunbaba always passed with various ceremony slaughter animals on the land to be planted.